Morphometric Study of Lumbar Intervertebral Spaces (discs) by Using MRI - Mansur, Dil Islam; Shrestha, Pragya; Maskey, Sunima; Sharma, Kalpana; Karki, Subindra; Kisiju, Trishna (Journal of Lumbini Medical College, 2020)
Introduction: The radiological space between two vertebrae is known as intervertebral space (height) which corresponds to the thickness of the intervertebral disc. Lumbar intervertebral disc is the most important structure which maintains the spinal function. An early diagnosis of pathological changes in disc has clinical significance. Hence the study aimed to determine normal height of the intervertebral disc space and effect of aging.Methods: It was a cross-sectional analytical study performed on 106 images of MRI scans of lumbar region. Dimensions of lumbar intervertebral spaces (discs) such as the anterior, middle, posterior intervertebral space height were measured in millimeter.Results: The mean anterior intervertebral space height was gradually increased from L1-L2 level (6.91 mm) to L5-S1 level (13.55 mm). The middle intervertebral space height increased from L1-L2 level (7.89 mm) to L4-L5 level (11.96 mm) whereas at L5-S1 level, there was a decrease (11.10 mm). Similarly, the posterior intervertebral space height showed an increment from L1-L2 level (5.52 mm) to L4-L5 level (8.09 mm) except at L5-S1 level, where it was decreased (6.94 mm). All mean values were found to be higher in males than in females except posterior intervertebral space height. The height of disc was increased up to third or fourth decade followed by a decrease.Conclusion: Knowing the normal lumbar intervertebral space height could be helpful for clinicians to diagnose and plan for proper treatment. It may also help to generate baseline data and to produce proper devices for Nepalese population.